2002
DOI: 10.1002/jcu.10074
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic evaluation of mammographically detected microcalcifications without a mass prior to stereotactic core needle biopsy

Abstract: In breast lesions that appear as microcalcifications without an associated mass on mammograms, pre-SCNB sonographic re-evaluation with a high-frequency transducer can depict microcalcifications, particularly the clustered ones, and can detect small associated masses. Although the absence of a sonographically detectable mass in areas of mammographically detected microcalcifications does not guarantee the absence of cancer, the presence of an associated mass on sonography should warrant close follow-up in the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…If calcifications are identified at US, US-guided core biopsy may, of course, be possible; its advantages over SCNB include a shorter procedure time and less patient discomfort, particularly in Asian women with small breasts, in whom positioning and compression during stereotactic biopsy are difficult. However, the reported success rate of pre-SCNB US in identifying calcifications is 35.8% (10), and although the success rate of US-guided core biopsy of calcifications identifiable at US has been reported to be up to 100% (11), the difficulty of accurately targeting the tiny specular reflectors, as well as interference in the multipass technique by introduced air, is well recognized. Accordingly, the biopsy of non-mass calcifications requires the use of stereotactic equipment.…”
Section: Discussionmentioning
confidence: 99%
“…If calcifications are identified at US, US-guided core biopsy may, of course, be possible; its advantages over SCNB include a shorter procedure time and less patient discomfort, particularly in Asian women with small breasts, in whom positioning and compression during stereotactic biopsy are difficult. However, the reported success rate of pre-SCNB US in identifying calcifications is 35.8% (10), and although the success rate of US-guided core biopsy of calcifications identifiable at US has been reported to be up to 100% (11), the difficulty of accurately targeting the tiny specular reflectors, as well as interference in the multipass technique by introduced air, is well recognized. Accordingly, the biopsy of non-mass calcifications requires the use of stereotactic equipment.…”
Section: Discussionmentioning
confidence: 99%
“…More frequently, 3D postprocessing has become important in assessment of vasculature. CHI US is already used to distinguish scars from recurrent tumours as well as in the optimisation of US-guided biopsies [14, 15, 20, 32]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that handheld breast US (HHUS) is useful in identifying malignant microcalcifications and provides effective guidance for percutaneous biopsy [789101112]. US-guided breast biopsy has several advantages over stereotactic biopsy, which include improved patient comfort, real-time visualization of needle placement, absence of radiation exposure, shorter duration of the procedure, and relatively low cost.…”
Section: Introductionmentioning
confidence: 99%